Genetic variation in zona pellucida-3 (ZP3) gene and its association with litter size variation in Kari sheep - Izaz Ali; Muhammad Ibrahim; Sohail Ahmad; Sher Hayat Khan; Ihtesham Ul Haq; Ibrahim A. Alhidary; Rifat Ullah Khan; Naseer Khan Momand; Marco Ragni (Animal Biotechnology)
Variation in litter size (LS) in sheep is linked to genetic factors, including the Zona pellucida-3 (ZP3) gene, which plays a role in ovine reproductive processes. This study examined the association between ZP3 gene variations and LS in Kari sheep. Two groups of 160 Kari ewes were analysed: one consistently producing singletons and another producing twins, with occasional triplets. Additionally, Madakhlasht sheep, which sometimes produce twins, and Balkhi sheep, which produce only singletons, were used as references. The entire ZP3 gene was amplified using PCR and sequenced at 30× with Next Generation Sequencing. Bioinformatics analysis identified 70 variants across the three breeds, located in upstream regions, introns, and exons. Notably, two point mutations and a six-nucleotide insertion were found upstream of the initiation codon in twin-producing Kari ewes, potentially affecting ZP3 expression and LS. Two missense mutations (I101L in exon 1 and R408H in exon 8) were heterozygous in twin-producing Kari ewes but homozygous in other groups, correlating with LS. Protein modelling suggested that the I101L mutation alters the binding site, potentially impacting protein function. These findings indicate that ZP3 gene variations influence reproductive efficiency and LS in sheep, with specific variants serving as potential markers for selective breeding to enhance LS.